Multi fingered robot hand in industrial robot application using tele-operation - Yaqub, Muhammad Atif (2013)
This research focuses on the working and development of wireless robotic hand system. In this research previously developed models have been studied. After analysis of those models, a better approach has been presented in this research. The objective of this research is to design and develop a tele-operated robotic hand system. The robotic hand is intended for providing solutions to industrial problems like robot reprogramming, industrial automation and safety of the workers working in hostile environments. The robotic hand system works in the master slave configuration where Bluetooth is being used as the communication channel for the tele-operation. The master is a glove, embedded with sensors to detect the movement of every joint present in the hand, which a human operator can wear. This joint movement is transferred to the slave robotic hand which will mimic the movement of human operator. The robotic hand is a multi fingered dexterous and anthropomorphic hand. All the fingers are capable of performing flexion, extension, abduction, adduction and hence circumduction. A new combination of pneumatic muscles and springs has been used for the actuation purpose. As a result, this combination reduces the size of the robotic hand by decreasing the number of pneumatic muscles used. The pneumatic muscles are controlled by the opening and closing of solenoid valves. A novel technique has been used in the robotic hand for tendon routing, which gives the ability of independence to all finger joints. The heart of all the control mechanism of the system is mbed microcontroller. The designed system was tested at different module levels. The results show the successful establishment of communication between master and slave at a rate of 10 packets per second, which was sufficient for smooth motion of the system. The amount of torque produced at all the joints in the robotic hand has been presented in this research. The posture tests have been performed in which two fingers were actuated which followed the master. This system has achieved motion of fingers without any tendon coupling problem. The system is able to replace the human industrial workers performing dexterous tasks.